Knowledge Level of Primigravida Pregnant Women About Postpartum Blues During Health Crisis Situations at Maradekaya Community Health Center in 2024 (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Alini, Meisyalla, L. N., & Novrika, B. (2024). Factors related to pregnant women's mental health in Pulau Rambai Village. Jurnal Ners, 8(1), 178-186. https://doi.org/10.37985/jpk.v1i1.389 American College of Obstetricians and Gynecologists. (2018). Committee Opinion No. 757: Screening for perinatal depression. Obstetrics & Gynecology, 132(5), e208-e212. https://doi.org/10.1097/AOG.0000000000002927 Arisjulyanto, D., Suharsono, T., & Firdaus, A. (2018). Disaster preparedness and maternal health emergency management in Indonesia. Indonesian Journal of Public Health, 13(2), 156-168. Aryani, D., Mulyani, S., & Ekawaty, F. (2024). Comparative analysis of video and leaflet media health education on increasing knowledge of young women about breast self-examination (BSE). Jurnal Ilmiah Ners Indonesia, 5(1), 51-61. https://doi.org/10.22437/Jini.V5i1.33449 Beck, C. T. (2023). Postpartum depression: A metasynthesis of qualitative research. Journal of Obstetric, Gynecologic & Neonatal Nursing, 52(3), 234-245. Chen, L., Wang, S., & Liu, M. (2022). Risk factors and prevention strategies for postpartum blues in Asian populations: A systematic review. Asian Journal of Psychiatry, 67, 102934. Dewi, V. N. L., & Sunarsih, T. (2011). Pregnancy care for midwifery. Salemba Medika. Garcia, R., Martinez, A., & Rodriguez, S. (2023). Digital interventions for perinatal mental health: A comprehensive review. Digital Health, 9, 20552076231165789. Haque, A. (2019). Factors affecting postpartum blues. Jurnal Ilmiah Psikologi, 15(2), 205-218. https://doi.org/10.51866/oa1037 Johnson, K., & Thompson, L. (2023). Maternal mental health literacy: Development and validation of a comprehensive assessment tool. Maternal and Child Health Journal, 27(4), 612-621. Kurniasari, A., & Astuti, T. (2019). The influence of midwifery services on quality of life of mothers and children. Jurnal Kebidanan Indonesia, 11(2), 123-136. Lee, S. H., Park, J., & Kim, Y. (2022). Cultural factors influencing postpartum mental health in Southeast Asian women. Culture, Medicine, and Psychiatry, 46(3), 587-605. Manurung, S., & Setyowati, S. (2021). Development and validation of the maternal blues scale through bonding attachments in predicting postpartum blues. Malaysian Family Physician, 16(1), 64-71. Ministry of Health Republic of Indonesia. (2019). Health profile of Indonesia 2019. Ministry of Health RI. Ministry of Health Republic of Indonesia. (2022). Mental health in pregnant and postpartum women. https://yankes.kemkes.go.id/View_Artikel/1022/Kesehatan-Mental-Pada-Ibu-Hamil-Dan-Pasca-Melahirkan Notoatmodjo, S. (2016). Obstetric science. EGC. Nursalam. (2017). Nursing research methodology: Practical approach (4th ed.). Salemba Medika. O'Connor, E., Rossom, R. C., Henninger, M., Groom, H. C., & Burda, B. U. (2019). Primary care screening for and treatment of depression in pregnant and postpartum women: Evidence report and systematic review for the US Preventive Services Task Force. JAMA, 315(4), 388-406. https://doi.org/10.1001/jama.2015.18948 Risnawati, H., Susilawati, D., & Dewi, K. (2018). Anxiety levels in primigravida pregnant women and postpartum blues risk. Indonesian Midwifery Journal, 6(2), 89-96. Rukiyah, A. Y. (2016). Community midwifery care. CV. Andi Offset. Siregar, T. H. (2022). Age factors and maternal readiness in preventing postpartum blues. Journal of Maternal Health, 8(3), 145-152. Smith, A., Brown, K., & Wilson, J. (2023). Health crisis preparedness in maternal care: Lessons from the COVID-19 pandemic. International Journal of Gynecology & Obstetrics, 160(2), 445-452. United Nations Population Fund. (2020). Impact of COVID-19 on maternal mental health: Global perspectives. UNFPA. World Health Organization. (2020). Maternal mental health and child health and development in low and middle income countries: Report of the WHO-UNFPA meeting. WHO Press.